The Pan African Vivax and Ovale Network (PAVON): Refocusing on Plasmodium vivax, ovale and asymptomatic malaria in sub-Saharan Africa. (October 2021) - Quaye, Isaac K.; Aleksenko, Larysa; Oeuvray, Claude; Yewhalaw, Delenasaw; Duah, Nancy; Gyan, Ben; Haiyambo, Daniel H.; Dongho, Ghyslaine Bruna Djeunang; Torgby, Ruth-Ayanful; Amoah, Linda; Hamid, Mahdi Abdel; Worku, Solomon; et al.
Abstract: The recent World Malaria report shows that progress in malaria elimination has stalled. Current data acquisition by NMCPs depend on passive case detection and clinical reports focused mainly on Plasmodium falciparum ( Pf ). In recent times, several countries in sub-Saharan Africa have reported cases of Plasmodium vivax (Pv) with a considerable number being Duffy negative. The burden of Pv and Plasmodium ovale (Po) appear to be more than acknowledged. Similarly, the contribution of asymptomatic malaria in transmission is hardly considered by NMCPs in Africa. Inclusion of these as targets in malaria elimination agenda is necessary to achieve elimination goal, as these harbor hypnozoites. The Pan African Vivax and Ovale Network (PAVON) is a new consortium of African Scientists working in Africa on the transmission profile of Pv and Po. The group collaborates with African NMCPs to train in Plasmodium molecular diagnostics, microscopy, and interpretation of molecular data from active surveys to translate into policy. Details of the mission, rational and modus operandi of the group are outlined. Graphical abstract: Unlabelled Image Highlights: Current malaria elimination efforts in Africa are focused only on Pf . Data to inform policy on malaria prevalence is from passive case detection and clinical presentation. Active case detection for Pv and Po is needed for elimination to succeed. Use of molecular tools to include asymptomatic infections will refine the true prevalence.